Estrategias de excavación y datación de arquitectura pública temprana. El caso de Cerro Lampay - Rafael Vega-Centeno Sara-Lafosse (Bulletin de l'Institut Français d'Études Andines, 2008)
The design of excavations at Cerro Lampay, as well as the strategy to recover organic samples for 14C analysis are presented in detail, noting the potentialities of a methodology where field options are closely linked with clear-cut and specific research objectives. The number of recovered dates (27) and its clustering in a time span of two centuries illustrates the importance of obtaining a reliable sample of organic materials, from well documented contexts, in order to get an accurate dating of early sites occupations.